HUBUNGAN PERSEPSI SISWA TERHADAP KEMAMPUAN GURU DALAM MENGGUNAKAN METODE DAN MEDIA PEMBELAJARAN - Desty Yusniarti S.A; Sumadi Sumadi; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2013)
The purpose of research to determine the relationship of students' perception of the ability of teachers to use teaching methods and media with student learning outcomes. Correlational research method used to determine the quantitative value of a variable or a connection between one variable with another variable. Data collection techniques using questionnaires given to 48 students of class XI as the research sample, which then results are analyzed using product moment correlation.Correlational research method used to determine the quantitative value of a variable or a connection between one variable with another variable. Data collection techniques using questionnaires given to 48 students of class XI as the research sample, which then results are analyzed using product moment correlation.The findings of the study were: 1) the ability of students Perception teachers use teaching methods have a strong and significant relationship with student learning outcomes in geography subjects in MAN 1 Bandar Lampung. The better perception students to the ability of teachers to use learning methods will be followed by an increase in student learning outcomes, 2) Perception students to the ability of teachers to use instructional media have a strong and significant relationship with student learning outcomes in geography subjects in MAN 1 Bandar Lampung. The better perception students to the ability of teachers to use instructional media it will be followed by an increase in student learning outcomes.Keywords: Perception of learning, Methods, Instructional Media